2023
DOI: 10.1039/d3tc01254a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable near-infrared piezochromic luminescence by effective substituent modification of D–A structures

Abstract: Piezochromic luminescent (PCL) materials have attracted extensive research interest due to their potential applications in mechanosensors, ink-free printing, optical data storage, optoelectronic devices, etc. However, there is rarely report about...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Aggregation-induced emission (AIE) molecules are ideal candidates for ultrawide NIR PCMs because they emit intense luminescence in the aggregated state and have a twisted stereo geometry that intrinsically suppresses the π–π interactions. 18–22 Yao et al recently reported AIE luminogens based on triphenylamine (TPA) showing significant emission red shifts of up to 200 nm (Fig. 1, MOTPAM: 550–751 nm) under increased hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation-induced emission (AIE) molecules are ideal candidates for ultrawide NIR PCMs because they emit intense luminescence in the aggregated state and have a twisted stereo geometry that intrinsically suppresses the π–π interactions. 18–22 Yao et al recently reported AIE luminogens based on triphenylamine (TPA) showing significant emission red shifts of up to 200 nm (Fig. 1, MOTPAM: 550–751 nm) under increased hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…1, MOTPAM: 550–751 nm) under increased hydrostatic pressure. 18 However, piezochromism in the NIR region is still not sufficiently wide. Hybridised local and charge transfer (HLCT) features have been proposed and utilised by Ma and Zhang to increase the emission efficiency and colour variation of dyes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the external stimulus sources, they are mainly divided into thermochromic, photochromic, electrochromic, piezoelectric materials, etc. In recent years, the development of color-changing materials has been very rapid. Due to their important application value and broad development prospects (applied in multiple fields including industry, textile, military, printing, architecture, and anti-counterfeiting labeling), color-changing materials have become one of the current research hotspots. Since its first proposal in 1932 (clearly defined as a series of quaternary pyridine salts derived from 4,4′-bipyridine), “viologen” has always been an important component of color-changing materials . One of the advantages of viologen is that it has three redox states, namely double cation (V 2+ ), free radical cation (V +* ), and neutral state (V 0 ) .…”
Section: Introductionmentioning
confidence: 99%
“…5 The precise optical, electrical, photophysical, electrochemical, and luminescent properties of D−A materials can be rationally controlled by constructing the appropriate electron-rich donor (D) and electron-deficient acceptor (A) units, 6 changing their chemical connections, and adjusting the space and molecular geometry in the D−A structures. 7 A large variety of organic semiconductors have been designed in D−A architectures, ranging from fluorescent/phosphorescent emitters, 8 host molecules, 9 thermally activated delayed fluorescence (TADF) materials, 10 stable radicals, 11 photovoltaic polymers, 3 to exciplexes. 12 Nevertheless, the extremely high diversity and flexibility of D−A structures are hard to harness, and totally different organic optoelectronic materials would result, which significantly limits the design and development of advanced optoelectronic D−A molecules.…”
mentioning
confidence: 99%
“…Combinations of donor and acceptor building blocks in different ways have been proposed, and subtle and complicated modulations of optoelectronic properties of organic semiconductors for the desired applications have been realized . The precise optical, electrical, photophysical, electrochemical, and luminescent properties of D–A materials can be rationally controlled by constructing the appropriate electron-rich donor (D) and electron-deficient acceptor (A) units, changing their chemical connections, and adjusting the space and molecular geometry in the D–A structures . A large variety of organic semiconductors have been designed in D–A architectures, ranging from fluorescent/phosphorescent emitters, host molecules, thermally activated delayed fluorescence (TADF) materials, stable radicals, photovoltaic polymers, to exciplexes .…”
mentioning
confidence: 99%